Assessing the Level of Emotional Intelligence among Future Vocational Workforce in Jordan - Khasawneh, Samer; Qablan, Ahmad; Al-Omari, Aieman; Abu-Tineh, Abdullah (Jordan Journal of Educational Sciences, 2007)
The purpose of this study was to assess the level of emotional intelligence among future vocational workforce in Jordan. A total of 150 vocational students participated in the study by completing the Emotional Intelligence Scale (EIS). The results indicated that vocational students have an acceptable moderate level of emotional intelligence on the five dimensions. Moreover, there were no significant differences between dimensions of emotional intelligence and the proposed demographic variables (gender and area of specialization). Finally, several recommendations were suggested for improving emotional intelligence among vocational students that can contribute to better job performance.